2014
DOI: 10.1186/1472-6963-14-145
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled telephone visits in the veterans health administration patient-centered medical home

Abstract: BackgroundThe Veterans Health Administration (VHA) patient-centered medical home model, Patient Aligned Care Teams (PACT), includes telephone visits to improve care access and efficiency. Scheduled telephone visits can replace in-person care for some focused issues, and more information is needed to understand how this mode can best work for primary care. We conducted a study at the beginning of PACT implementation to elicit stakeholder views on this mode of healthcare delivery, including potential facilitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…While not focused specifically on rural, another study conducted in the VHA found favorable perceptions of telephone visits for routine care not requiring a physical from both Veterans and primary care providers. 3 Relatedly, McKinstry et al 6 found that telephone consultations were often used by rural patients and staff to maintain more regular contact and to avoid having to travel. They also reported that, unlike urban patients, rural patients were more likely to use telephone consultations to determine whether an in-person visit was necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not focused specifically on rural, another study conducted in the VHA found favorable perceptions of telephone visits for routine care not requiring a physical from both Veterans and primary care providers. 3 Relatedly, McKinstry et al 6 found that telephone consultations were often used by rural patients and staff to maintain more regular contact and to avoid having to travel. They also reported that, unlike urban patients, rural patients were more likely to use telephone consultations to determine whether an in-person visit was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…1 The use of telephone visits is 1 strategy being promoted to enhance access to primary care that does not require in-person visits. 2,3 A recent study from the Veterans Health Administration (VHA) found that the use of telephone communication is strongly associated with higher patient perceptions of access. 4 To our knowledge, no studies have specifically examined rural patients' perceptions of access associated with telephone visits, especially for clinics with longer wait times for in-person visits.…”
mentioning
confidence: 99%
“… 6 Focus groups performed before the implementation of scheduled telephone visits at the Veteran’s Administration primary care clinics found that patients viewed them as potentially beneficial for routine care but feared losing touch with their providers. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Novice NPs may enter practice lacking the skills and confidence to interpret and effectively communicate laboratory results and to return patient telephone calls. Providing more venues that improve access to care, such as through telephone visits, is integral in meeting the needs of patients (Adler-Milstein, Kvedar, & Bates, 2014;Sperber et al, 2014). Telephone visits also can be used for lifestyle modification counseling and episodic or nonurgent visits not requiring a physical examination (Kyanko et al, 2018).…”
mentioning
confidence: 99%